Progress in Metallic Alloys - Glebovsky, Vadim (IntechOpen, 2016)
In general, metallic alloys are the interdisciplinary subject or even an area that cover physics, chemistry, material science, metallurgy, crystallography, etc. This book is devoted to the metallic alloys. The primary goal is to provide coverage of advanced topics and trends of R&D of metallic alloys. The chapters of this book are contributed by the respected and well-known researchers which have presented results of their up-to-date metallic alloys technologies. The book consists of two blocks filled with 10 chapters which provide the results of scientific studies in many aspects of the metallic alloys including the studies of amorphous and nanoalloys, modeling of disordered metallic alloys, superconducting alloys, differential speed rolling of alloys, meta-magnetic Heusler alloys, etc. The book is of interest to both fundamental research and practicing scientists and will prove invaluable to all chemical and metallurgical engineers in process industries, as well as to students and engineers in industry and laboratories. We hope that readers will find this book interesting and helpful for the work and studies. If so, this could be the best pleasure and reward for us.